2019
DOI: 10.1108/sef-02-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin, Litecoin, and the Euro: an annualized volatility analysis

Abstract: Purpose This paper aims to empirically investigate the volatility of Bitcoin, Litecoin and the Euro. Design/methodology/approach The authors use quantitative methodologies to assess the annualized volatility of two cryptocurrencies and one international fiat currency. The exchange rate of the currencies is monitored on a daily basis using 1,460 observations from January 1, 2014 to December 31, 2017. The models used include the augmented Dickey–Fuller test, Akaike Information Criteria, autocorrelation functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Bitcoin reports the lowest risk measures of all coins, specifically, regarding standard, semi and downside deviation, historical VaR and ES. Similar results by Miglietti et al (2019) indicate that Bitcoin has a rather low-risk profile compared to other cryptocurrencies such as Litecoin. Because of the fact, Bitcoin was the first cryptocurrency launched and, thus, making it the most matured of all, investors highly appreciate it as a safe haven, which has also been empirically proved (Bouri et al, 2017;Chan et al, 2019).…”
Section: Descriptive Statisticssupporting
confidence: 67%
“…Bitcoin reports the lowest risk measures of all coins, specifically, regarding standard, semi and downside deviation, historical VaR and ES. Similar results by Miglietti et al (2019) indicate that Bitcoin has a rather low-risk profile compared to other cryptocurrencies such as Litecoin. Because of the fact, Bitcoin was the first cryptocurrency launched and, thus, making it the most matured of all, investors highly appreciate it as a safe haven, which has also been empirically proved (Bouri et al, 2017;Chan et al, 2019).…”
Section: Descriptive Statisticssupporting
confidence: 67%
“…As we know from the previous studies that cryptocurrency markets are highly volatile markets and the price of the crypto’s might change over time (Bouri et al , 2018; Miglietti et al , 2020; Sahoo, 2017). So, the study tries to check the break period of the data series.…”
Section: Empirical Analysismentioning
confidence: 99%
“…However, the COVID-19 relationship in cryptocurrency markets remains unexplored. Bitcoin and other cryptocurrencies are considered as financial asset and highly volatile (Bouoiyour et al , 2014; Bouri et al , 2018; Sahoo, 2017; Kostika and Laopodis, 2019; Hu et al , 2019; Miglietti et al , 2020; Pelster et al , 2019; Sahoo, 2020) and better hedging capabilities over other financial assets such as stocks and US dollar (Dyhrberg, 2016). As a result, during the pandemic, investors have tried to diversify their portfolio toward cryptocurrencies to take short-term gain.…”
Section: Introductionmentioning
confidence: 99%
“…Buchholz, et al, (2012) found that before the peak of the bubble, volatility had a statistically significant positive effect on price of Bitcoin. Miglietti, et al, (2019) indicate that the Litecoin is more volatile than Bitcoin. Vardar and Aydogan (2019) reveal the existence of the positive unilateral return spillovers from the bond market to Bitcoin market.…”
Section: Literature Review:-mentioning
confidence: 99%